Management and Outcomes of a Foot Ulcer Caused by Extravasation: A Case Report - Palmieri, Isabella Pia; Ferrazza, Paolo; Grasso, Margherita (International Journal of Innovative Research in Medical Science, 2024)
Extravasation occurs during an intravenous infusion (IV), and the severity of the tissue damage depended on factors like the volume of leaked solution, infusion site, patient characteristics, and the infused agent's toxicity. We herein present the case of a 52-year-old woman who developed a foot ulcer due to unexpected extravasation and highlight the successful use of Aquavis® an innovative product that, when combined with other treatments, shows promise in promoting wound healing and addressing related challenges.